ANALISIS LIFE STYLE BERDASARKAN FAKTOR KARAKTERISTIK PENDERITA HIPERTENSI DI RW. 09 DESA SRUNI GEDANGAN SIDOARJO JAWA TIMUR INDONESIA - umdatus soleha (Universitas Nahdlatul Ulama Surabaya, 2019)
Life style can help control blood pressure for people with hypertension, but to have a healthy lifestyle is not an easy thing for most people. A healthy life style is one of the capital in the management of non-pharmacological hypertension. Modernization tends to be a big obstacle in having a healthy life style. The purpose of this study was to analyze life style based on the characteristics of hypertensive patients at RW.09 Sruni Village, Gedangan, Sidoarjo. This study was using descriptive cross sectional research design. The population in this study were hypertensive patients with 143 people, a sample of 105 people taken through simple random sampling technique. The research variables are life style, age and gender. The instrument of this study used a questionnaire, data analysis was carried out using descriptive analysis. The results showed that of the 105 respondents most of the respondents were women, namely 53.3%, the age of respondents almost half were in the age range of 56-65 which was 43.8%, the life style of the sufferers mostly had an unhealthy life style of 63.8%. A healthy life style is an important factor in helping control blood pressure. For women and men, they should both have good efforts in improving the quality of life style. Hypertension sufferers in RW.02 Sruni Village, Gedangan Sidoarjo, are important in controlling blood pressure through medication and having a healthy life style. Regulating life style by not consuming fast food, regular activities, maintaining ideal body weight, regular exercise, not smoking and having a good stress handling mechanism are highly recommended for sufferers.